Parenting Management Of Santri Mutawasithoh Islamic Boarding School Nurul Huda Purbalingga - Ali Mubarok (Prosiding University Research Colloquium, 2021)
The parenting style applied in the dormitory tends to be authoritarian or centered on onefigure only. Through this coaching style, it is hoped that students will obey and develop inthe direction expected by the Islamic boarding school. The authoritarian parenting styleaffects the condition of students living in Islamic boarding schools when compared to otherparenting patterns such as permitive and democratic. One of the prominent influences onstudent discipline. Therefore, caregivers must familiarize students with a series ofboarding school activities and obey the applicable regulations. Strategies to achieve thegoal of disciplining students, among others, are through the example of their caregiversthrough advice, guidance and ta'zir (punishment). Therefore, it is very interesting to takea study on the pattern of parenting held at the Islamic Islamic Boarding School NurulHuda Purbalingga. Because the number of students reaches 1,200 students.This research method uses a qualitative approach, with a field research model.Researchers went directly to the pesantren to dig up data and information throughobservation and interviews with related parties, such as the head of the foundation, mudir(kiai), and the student body or caregiving department, then the results were analyzedusing descriptive analysis. This research was conducted at the Islamic Boarding SchoolNurul Huda Purbalingga, Mutawashitoh son unit.The results showed that the Islamic Boarding School Nurul Huda Purbalingga, especiallythe Mutawasithoh unit in its care had been managed well and neatly, from planning,organizing, monitoring and evaluating. The pattern of parenting organization in MutiqNurul Huda is that a mudir (kiai) gives parenting tasks to the principal, then the principaldivides the tasks to the curriculum section and the santri section to carry out these tasks.Kiai is a figure who is always followed and used as an example by his students. A Kiaimust have strong management and leadership knowledge in parenting. So that thecharacter of the students can be formed in accordance with the vision, mission and goalsthat have been proclaimed.The pattern of santri in nurturing students is to always provide direction before theactivity begins, provide training and assignments to students, always direct students tofollow and obey all existing regulations, always be a role model for students and create aconducive environment for student learning.In the care of the students of Mutawasithoh Nurul Huda, there are factors that supportand hinder. Among the supporting factors are the figure of a kiai, adequate humanresources, a dormitory system that makes it easier for students to care for students and acomfortable and clean boarding environment so that students can study well. Theinhibiting factor is the problem of funding. Many guardians of students are late in payingtuition fees, so that it affects the smooth accommodation and funding of parentingactivities.